Getting to Know the Basic Concepts of Sharia Investment for More Sustainable Finance - Ghaniva, Eva Milatul (ICO EDUSHA, 2024)
This article aims to explore and understand the basic concepts of sharia investment as a sustainable alternative in the modern financial world. Using qualitative research methods through a literature study approach, this article examines various relevant sources related to the basic principles of sharia investment, the instruments used, and their relevance in encouraging the creation of a fairer and more sustainable financial system. This research includes an analysis of the main principles in sharia investment such as the prohibition of riba (interest), gharar (uncertainty), and maysir (gambling), as well as the application of these principles in investment instruments such as sharia shares, sukuk, and sharia mutual funds. This article also discusses how sharia investment can be a solution in creating more responsible and sustainable finance, especially in facing increasingly complex global economic challenges. The results of the literature study show that sharia investment not only meets financial needs, but also pays attention to social and environmental impacts, which makes it relevant in the context of sustainable finance. These findings indicate the great potential of sharia investment to contribute to more inclusive and sustainable economic development.